BERNULLI SONLARINING BA’ZI TADBIQLARI - Prenov, B.B.; Abdullayev, J.Sh.; Xaldibayeva, I.T. (SCIENCE and SOCIETY, 2025)
In this article, there are considered some applications of complex variable power series, in which with the help of Bernoulli’s numbers, the method of calculating the sum p+2^p+3^p+...+n^p=Σj^p for an arbitrary natural number p is given. The article may be of interest to senior undergraduate students majoring in mathematics and master's degree students.
Keywords: Bernoulli numbers; power series; radius of convergence; terminating sum